Oxygen‐ion conduction in scandia‐stabilized zirconia‐ceria solid electrolyte (xSc2O3–1CeO2–(99−x)ZrO2, 5 ≤ x ≤ 11). Issue 2 (25th October 2016) - Kumar, Ashutosh; Jaiswal, Abhishek; Sanbui, Mohit; Omar, Shobit
Abstract: Solid oxide fuel cells (SOFCs) operating at intermediate temperature (500°C‐700°C) provide advantages of better durability, lower cost, and wider target application market. In this work, we have studied Sc2 O3 (5‐11 mol%) stabilized ZrO2 –CeO2 as a potential solid electrolyte for application in IT‐SOFCs. Lower Sc2 O3 doping range than the traditional 11 mol% Sc2 O3 ‐stabilized ZrO2 is an interesting research topic as it could potentially lead to an electrolyte with reduced oxygen vacancy ordering, lower cost, and higher mechanical strength. XRD and Raman spectroscopy was used to study the phase equilibrium in ZrO2 –CeO2 –Sc2 O3 system and impedance spectroscopy was done to estimate the grain, grain boundary, and total ionic conductivities. Maximum for the grain and grain‐boundary conductivities as well as the tetragonal‐cubic phase boundary was found at 8‐9 Sc2 O3 mol% in ZrO2 ‐1 mol% CeO2 system. It is suggested that the addition of 1 mol% CeO2 in the ZrO2 host lattice has improved the phase stability of high‐conductivity cubic and tetragonal phases at the expense of low‐conductivity t′‐ and β‐phases. Abstract :